Developing intercultural empathy through a strategy-based simulation in intermediate Spanish. Issue 6 (1st November 2020) - Drewelow, Isabelle; Finney, Sara
ABSTRACT: This article reports on using a strategy-based simulation designed to engage intermediate Spanish learners with issues of drug trafficking and violence at the US-Mexico border as an avenue to cultivate an empathetic frame of mind and global perspectives. Using self-reported responses on pre- and post-reflections as well as face-to-face and digital interactions, the study examines how adopting the role of a character and promoting an agenda affected learners' viewpoints and interpretations of the issues of drug trafficking and border violence. Through embracing new subjectivities in their character roles, data analysis revealed that a majority of learners re-evaluated their views and progressed toward a more global perspective after participation in the simulation. Nonetheless, some learners' ability to fully immerse themselves into their character role was hindered by perceived obstacles present in the non-traditional curriculum. The article concludes with implications related to the promotion of global citizenry.